Do environmental influences alter motor abilities acquisition? A comparison among children from day-care centers and private schools - Karla Mônica F. T. de Barros; Andreza Gusmão Câmara Fragoso; Andréa Lemos Bezerra de Oliveira; José Eulálio Cabral Filho; Raul Manhães de Castro (Arquivos de Neuro-Psiquiatria)
Development occurs in a proper rhythm as result of genetic inheritance and environment factors. This study had the aim to identify some environmental risk factors for the motor development in two groups of healthy children. 100 pre-school aged (five years children) from two day-care centers and a private school were evaluated, in Recife-PE. All the children underwent to a motor skills assessment and their parents answered a questionnaire. The children from the public nursery remained behind in fine motor skills. The results showed that the biologically healthy children development can suffer negative influence of the environmental risk factors. In this research these factors were: the father absence, improper toys use to the correct age, the place were the child was kept in the early childhood, the lack of pedagogical guidance and extra-parental socialization and low familiar socioeconomic status.